2001
DOI: 10.1002/1097-0142(20010415)91:8<1479::aid-cncr1155>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Experience of 1000 patients who underwent hepatectomy for small hepatocellular carcinoma

Abstract: BACKGROUND Recently, the implementation of screening programs using α‐fetoprotein (AFP) and ultrasonography in high risk populations has identified increasing numbers of patients with small hepatocellular carcinoma (small HCC). The aim of this study was to summarize the authors' experience in patients who underwent hepatectomy for small HCC and the factors that influence or improve long term survival. METHODS The study included 1000 patients who underwent hepatectomy for small HCC (≤ 5 cm) and compared them wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
161
1
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(176 citation statements)
references
References 20 publications
9
161
1
5
Order By: Relevance
“…Tumor size is considered an important factor that influences the long-term survival rate of patients with HCC after they undergo hepatectomy. 24 It has been reported that the percentage of poorly differentiated tumor cells is higher in large HCC tumors; therefore, proliferative activity and Edmondson grade often were higher in large HCC tumors. 25 However, the cytogenetic alterations that contribute to this feature remain obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size is considered an important factor that influences the long-term survival rate of patients with HCC after they undergo hepatectomy. 24 It has been reported that the percentage of poorly differentiated tumor cells is higher in large HCC tumors; therefore, proliferative activity and Edmondson grade often were higher in large HCC tumors. 25 However, the cytogenetic alterations that contribute to this feature remain obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic patients with early HCC who have negative serum markers (AFP and PIVKA-II) are usually not diagnosed until the advanced stage. Early diagnosis of HCC could greatly improve the outcome of surgical treatments for HCC, with better long-term survival and reduced recurrence risk [3]. Therefore, search for effective markers for HCC is a field of intense research.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination with hepatitis B surface antigen and IFN therapy for hepatitis C may reduce the incidence of HCC in the future (3,4), but effective treatment for HCC in hepatitis-prevalent countries such as China, where one-third of new cases arise (5,6), is urgently needed. Curative treatments such as hepatic resection, orthotopic liver transplantation, or percutaneous regional treatments offer the only chance of cure, but most cases are ineligible at diagnosis due to advanced tumor stage or poor liver function (6 -14).…”
Section: Introductionmentioning
confidence: 99%
“…Curative treatments such as hepatic resection, orthotopic liver transplantation, or percutaneous regional treatments offer the only chance of cure, but most cases are ineligible at diagnosis due to advanced tumor stage or poor liver function (6 -14). Furthermore, the high frequency of postoperative recurrence decreases the long-term survival rate (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%